Tobacco use and household expenditures on food, education, and healthcare in low- and middle-income countries: a multilevel analysis. (December 2015) - Do, Young; Bautista, Mary
Abstract Background The majority of one billion smokers worldwide live in low- and middle-income countries (LMICs) and the highest proportion of smokers in most of these countries belong to the lower socioeconomic groups. This study aimed to investigate the associations between tobacco use within households and expenditures on food, education, and healthcare in LMICs. Methods Using data from the World Health Survey, this cross-sectional study included a sample of 53, 625 adult males aged <60 years from 40 LMICs. Multilevel, mixed-effects linear regression was used to determine the association between current tobacco use status of the main income provider (daily; occasional; no use) and three categories of (logged) household expenditures: food, education, and healthcare; controlling for age, level of education, household wealth quintile, marital status, urban–rural setting, country-level income group, and region. Results In the preferred random-slope models that controlled for covariates, daily tobacco use was associated with lower household expenditures on education and healthcare by 8.0 % (95 % confidence interval: −12.8 to –3.2 %) and 5.5 % (−10.7 to –0.3 %), respectively. The association between tobacco use and food expenditure was inconsistent across models. Conclusions Tobacco use in LMICs may have a negative influence on investment in human capital development. Addressing the tobacco use problem in LMICs could benefit not only the health and economic well-being of smokers and their immediate families but also long-run economic development at a societal level.